Identifying air quality monitoring deserts in the United States - Nelson A. Roque; Hailey Andrews; Alexis R. Santos-Lozada (Proceedings of the National Academy of Sciences, 2025)
Air quality is associated with adverse health outcomes and mortality risk. While most research has focused on the association between air quality estimates and these outcomes, little is known about the presence of air quality monitoring sites across the United States or the place-level characteristics associated with such placements. We classify counties without a monitoring station as air quality monitoring deserts. Using the Environmental Protection Agency’s AirData active sites directory, we determine the number and location of monitoring deserts. We then study whether demographic and socioeconomic characteristics are associated with the likelihood of a county being a monitoring desert. Our results indicate that 1,848 or 58.8% of US counties are an air quality monitoring desert, covering about 40% of the nation’s land area. Our estimates suggest that more than 50 million people or 15.3% of the population live in air quality monitoring deserts. Rural and counties with higher proportions of historically minoritized groups have higher odds of being a monitoring desert. Regionally speaking, air quality monitoring deserts are highly concentrated within the Midwest and the South. These findings highlight gaps in air quality monitoring in the United States. Identifying and addressing air quality monitoring deserts across the United States will allow us to better understand air quality across the nation and expand current knowledge of its impact on national health and well-being.